Exploring service innovation and value creation: The critical role of network relationships. (7th August 2017) - Hsiao, Yung-Chang
Abstract: This study examines the role of service innovation, including service process, Information Technology infrastructure and customer acuity, on customer satisfaction from the network relationships perspective. This study tests the hypotheses in a sample of 136 companies, which is drawn from top 5, 000 Taiwanese firms listed in the 2015 yearbook published by the China Credit Information Service Incorporation. The results indicate that service innovation is positively related to network relationships, and that network relationships have a positive effect on customer satisfaction. Also, the results provide evidence that network relationships play a mediating role between service innovation and customer satisfaction. The findings of this study contribute to the theoretical development of a conceptual model for explaining the interrelationships among service innovation, network relationships, and customer satisfaction. The empirical evidence of the Sobel test, in line with Baron and Kenny's procedure and bootstrap analysis supports the process-oriented view and indicates that network relationships mediate the effect of service innovation on customer satisfaction. Finally, this study discusses managerial implications and highlights future research directions.